Mitochondrial genetic diversity, selection and recombination in a canine transmissible cancer - Strakova, Andrea; Leathlobhair, Máire Ní; Wang, Guo-Dong; Yin, Ting-Ting; Airikkala-Otter, Ilona; Allen, Janice L.; Allum, Karen M.; Bansse-Issa, Leontine; Bisson, Jocelyn L.; Domracheva, Artemio Castillo; De Castro, Karina F. [UNESP]; Corrigan, Anne M.; et al. (eLife, 2016)
Canine transmissible venereal tumour (CTVT) is a clonally transmissible cancer that originated approximately 11,000 years ago and affects dogs worldwide. Despite the clonal origin of the CTVT nuclear genome, CTVT mitochondrial genomes (mtDNAs) have been acquired by periodic capture from transient hosts. We sequenced 449 complete mtDNAs from a global population of CTVTs, and show that mtDNA horizontal transfer has occurred at least five times, delineating five tumour clades whose distributions track two millennia of dog global migration. Negative selection has operated to prevent accumulation of deleterious mutations in captured mtDNA, and recombination has caused occasional mtDNA re-assortment. These findings implicate functional mtDNA as a driver of CTVT global metastatic spread, further highlighting the important role of mtDNA in cancer evolution.